Ecuador : Request for Purchase under the Rapid Financing Instrument and Cancellation of Arrangement under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Ecuador. (IMF Staff Country Reports; Country Report ;, 2020)
This chapter presents Ecuador's Request for Purchase Under the Rapid Financing Instrument (RFI) and Cancellation of Arrangement Under the Extended Fund Facility (EFF). Ecuador is facing urgent and immediate balance of payment (BOP) needs driven by the sharp propagation of the coronavirus disease 2019 outbreak-Ecuador is one of the hardest hit countries in Latin America-a plummeting of oil prices, and a dramatic collapse of global demand. In the near term, the authorities have taken significant measures to contain the spread of the virus and mitigate the socio-economic impact. Containment measures include the closing of schools and universities, public spaces and noncritical commercial activities, halting public transport, and imposing a nationwide curfew. Additional support from other external partners will be required and critical to close the remaining financing gap and ease budget constraints. The RFI will help Ecuador finance the much-needed health and social assistance spending and catalyze financing from other multilateral financial institutions.